Analysis of IVF/ICSI-FET Outcomes in Women With Advanced Endometriosis: Influence on Ovarian Response and Oocyte Competence - Li, Anji; Zhang, Jie; Kuang, Yanping; Yu, Chaoqin (Frontiers in Endocrinology, 2020)
Aims: To determine the impact of advanced endometriosis on in vitro fertilization/intracytoplasmic sperm injection and frozen-thawed embryo transfer (IVF/ICSI-FET) outcomes and analyze the influencing factors. Methods: A retrospective study was conducted on sterile women with ovarian endometrioma(s) (OMA), including patients undergone laparoscopic cystectomy (n=224, 224 IVF/ICSI cycles, 205 FET cycles) and aspiration (n=139, 139 IVF/ICSI cycles, 148 FET cycles), peritoneal endometriosis (n=96, 96 IVF/ICSI cycles, 89 FET cycles) and tubal factors (n=360, 360 IVF/ICSI cycles, 474 FET cycles). Our main outcomes included the number of MII oocytes retrieved, fertilization rate, the number of viable embryos, viable embryo rate per oocyte retrieved in oocyte retrieval cycles, and clinical pregnancy rate per transfer, live birth rate per transfer and cumulative clinical pregnancy rate of this oocytes retrieval cycle in FET cycles. Finally, binary logistic regression analysis was performed to generate a prediction model for cumulative clinical pregnancy. Results: The results showed that significantly less MII oocytes retrieved and viable embryos and lower viable embryo rate and cumulative clinical pregnancy rate were observed in women with endometriosis compared with the control. Women with peritoneal endometriosis had lower fertilization rate and viable embryo rate per oocyte retrieved than patients with OMA (all p＜0.05). However, the pregnancy outcomes were not significantly different between the two phenotypes. The patients undergone laparoscopic cystectomy had less MII oocytes retrieved and viable embryos compared with those with intact endometrioma(s) but no significant difference in pregnancy outcomes between the two types of OMA patients. By binary logistic regression analysis, antral follicle count (AFC) was found to be an independent factor associated with cumulative clinical pregnancy in this oocytes retrieval cycle [OR = 1.054; 95% CI: 1.011-1.100; p=0.014] and the AFC prediction model of cumulative clinical pregnancy was established, with the AUC was 0.60. Conclusions: Our data supported that advanced endometriosis has negative effect on cumulative clinical pregnancy per oocytes retrieval cycle and AFC is an independent predictor, which is mainly caused by poor ovarian response associated with OMA per se or its surgery and the damage of peritoneal endometriosis to oocytes maturation.